Cognitive impairment from early to middle adulthood in patients with affective and nonaffective psychotic disorders. Issue 1 (4th January 2019) - Mollon, Josephine; Mathias, Samuel R.; Knowles, Emma E. M.; Rodrigue, Amanda; Koenis, Marinka M. G.; Pearlson, Godfrey D.; Reichenberg, Abraham; Barrett, Jennifer; Denbow, Dominique; Aberizk, Katrina; Zatony, Molly; Poldrack, Russell A.; et al.
Abstract: Background: Cognitive impairment is a core feature of psychotic disorders, but the profile of impairment across adulthood, particularly in African-American populations, remains unclear. Methods: Using cross-sectional data from a case–control study of African-American adults with affective ( n = 59) and nonaffective ( n = 68) psychotic disorders, we examined cognitive functioning between early and middle adulthood (ages 20–60) on measures of general cognitive ability, language, abstract reasoning, processing speed, executive function, verbal memory, and working memory. Results: Both affective and nonaffective psychosis patients showed substantial and widespread cognitive impairments. However, comparison of cognitive functioning between controls and psychosis groups throughout early (ages 20–40) and middle (ages 40–60) adulthood also revealed age-associated group differences. During early adulthood, the nonaffective psychosis group showed increasing impairments with age on measures of general cognitive ability and executive function, while the affective psychosis group showed increasing impairment on a measure of language ability. Impairments on other cognitive measures remained mostly stable, although decreasing impairments on measures of processing speed, memory and working memory were also observed. Conclusions: These findings suggest similarities, but also differences in the profile of cognitive dysfunction in adults with affective and nonaffective psychotic disorders. Both affective and nonaffective patients showed substantial and relatively stable impairments across adulthood. The nonaffective group also showed increasing impairments with age in general and executive functions, and the affective group showed an increasing impairment in verbal functions, possibly suggesting different underlying etiopathogenic mechanisms.